Альгофлора пещер и гротов Национального природного парка «Подольские Товтры» (Украина) - Виноградова, О.Н.; Михайлюк, Т.И. (Альгология, 2009)
В результате изучения водорослей пещер и гротов Национального природного парка „Подольские Товтры” выявлено 86 видов (87 внутривидовых таксонов) из отделов: Cyanoprokaryota – 35; Chlorophyta – 35; Streptophyta – 3; Xanthophyta – 4; Eustigmatophyta – 2; Bacillariophyta – 7, среди которых 56 новых для данной территории видов, 8 – новых для Украины. В гротах (67 видов), как экологически более комфортных местообитаниях, преобладали зеленые водоросли (49-58 % видового состава), тогда как цианопрокариоты составляли 11-29 %. Альгофлора пещер (46 видов) характе-ризовалась меньшим видовым разнообразием и значительно большей долей цианопрокариот (40-70 % видового состава). Исследования показали, что интенсивность освещения является ключевым фактором в распределении водорослей в изученных спелеообъектах. Систематическая структура исследованной альгофлоры пещер оказалась близкой к таковой спелеообъектов Европы, особенно Венгрии. In five limestone speleoobjects (two caves and three grottoes) in the National Nature Park “Podilsky Tovtry”, 86 species (87 infraspecies taxa) were revealed. They belong to Cyanoprokaryota (35 species), Chlorophyta (35), Bacillariophyta (7), Xanthophyta (5), Streptophyta (3), and Eustigmatophyta (2). Fifty-six species are first cited for the National Nature Park, eight species are new for the Ukraine, and eight species are noteworthy floristic records. In the grottoes 67 species were recorded; in these ecologically more comfortable habitats green algae prevailed (49-58 % of species composition). Cyanoprocaryotes consisted of 11-29 %. A peculiar feature of the algal flora of caves was lower species diversity (46 species) and a much greater percent of cyanoprocaryotes (40-70 % of species composition). Light intensity was found to be the key factor influencing distribution of algae in the studied speleotops. Taxonomic structure of studied algal flora of the caves has much in common with other European caves, especially the Hungarian caves. A comparison of algal flora of studied grottoes with those inhabiting granite rocks on limestones had greater diversity of cyanoprocaryotes and aerophytic-edaphic species from the classes Trebouxiophyceae and Chlorophyceae due to high porosity, water-retaining capacity, and the high рН of this substrate.